Comprehensive Review of Binder Matrices in 3D Printing Construction: Rheological Perspectives - Yeşim Tarhan; İsmail Hakkı Tarhan; Remzi Şahin (Buildings)
Three-dimensional printing technology is transforming the construction industry, which is increasingly turning to advanced materials and techniques to meet environmental and economic challenges. This comprehensive literature review evaluated various binder materials, including cement, geopolymers, earthen materials, supplementary cementitious materials, polymers, and biopolymers, with a focus on their environmental impacts and rheological properties. The study revealed an increasing interest in cementitious binders, which deliver essential structural strength and exhibit a wide range of yield stress values (15 to 6500 Pa), influenced by binder type and supplementary materials such as nanoclay. However, the significant CO2 emissions associated with cement pose major sustainability challenges. As a sustainable alternative, geopolymers demonstrate lower yield stress values (800 to 3000 Pa) while ensuring adequate buildability for vertical printing and reducing environmental impact. These findings underscore the need to adopt sustainable binder matrices to align 3D printing construction practices with global sustainability goals.